V-interESP - Using Videos to Enhance ESP Students' Learning Experience: International Joint Teaching and Research - Vieira Vasconcelos, Sandra (2022)
Addressing the growing need to re-examine current approaches and teaching methods within the scope of ESP, this paper starts by describing the preliminary states of V-interESP – an international joint research project involving students and faculty from Lithuania, Portugal and Serbia. This project has two primary goals: to understand the role digital technology, and particularly videos, can play in enhancing students’ learning experiences within ESP settings; and to promote the study participants’ creativity, intercultural awareness and communication. Thus, in this study, the authors present preliminary research findings, based on the students’ answers to an entry questionnaire. Data focusses on students’ profiles and their perceived potential of using video to learn ESP, in particular regarding student motivation and the development of communication skills, as well as creative abilities.